Radiographic Assessment Checklist for Implant Placement - Talati, Meenakshi; Shah, Rohit; Mitra, Dipika; Rodrigues, Silvia; Shetty, Gaurav; Prithyani, Saurabh; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Dental implants are gaining immense popularity and wide acceptance because they not only replace lost teeth but also provide permanent restorations that do not interfere with oral function or speech or compromise the self-esteem of a patient. Appropriate treatment planning for replacement of lost teeth is required and imaging plays a pivotal role to ensure a satisfactory outcome. The development of pre-surgical imaging techniques and surgical templates helps the dentist place the implants with relative and accurate ease. In this article, authors have proposed a checklist for radiographic assessment for implant placement during various stages of the implant procedure.